Reentrant surface melting of colloidal hard spheres. - Dullens, R; Kegel, W (2004)
Concentrated suspensions of model colloidal hard spheres at a wall were studied in real space by means of time-resolved fluorescence confocal scanning microscopy. Both structure and dynamics of these systems differ dramatically from their bulk analogs (i.e., far away from a wall). In particular, systems that are a glass in the bulk show significant hexagonal order at a wall. Upon increasing the volume fraction of the colloids, a reentrant melting transition involving a hexatic structure is observed. The last observation points to two-dimensional behavior of matter at walls.